Scattering and attenuation of ultrasonic - 406943 Koh, Yeong Ting; Md. Supar Rohani, supervisor; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains (Fizik industri)) - Universiti Teknologi Malaysia, 2008